أفق التّلقّي:بين الوصف البلاغي والوقع الجمالي –قراءة في مقامات بديع الزمان الهمذاني-. - عون, نعيمة (roa; Vol 2 (2021): مجلة رؤى في الآداب والعلوم الإنسانية, 2021)
تهدف الدّراسة الحاليّة إلى التعرف على مصطلح التّلقي في سيرورة اللقاء الّذي يجمع بين التّلقي في التّراث البلاغي العربي،  كمفهوم يبّين الفهم لنوعية العلاقة بين المرسل ( المخاطِب) والمرسل إليه (المخاطَب ) والرسالة (الخطاب)، و قضية التّأثير والتّأثر الّتي تَبناها النُّقاد العرب اليوم، ومن بينها القضية الاصطلاحية لنظرية التلقي الغربية (مدرسة كونستانس الألمانية)، وهو نموذج جديد بدأ يفرض نفسه على ساحة الدّراسات الجماليّة الأدبية من خلال هرمينوطيقا التّلقي عند ياوس وفينومينولوجيا التّلقي عند أيزر ، لهذا شمل موضوع الدّراسة تقصي ملامح التلقي   باعتباره فعل إنساني قديم قدم الإبداع، في ضوء الموروث الأدبيّ – فن المقامة - وتوضيح تفاعل بعض المفاهيم والمصطلحات  لظاهرة التلقي قديما وحديثا ، من خلال تنوع أنماط التلقي عبر الظرفيّة التّاريخية.     من هنَا نتساءل : هل عرف تراثنا العربي مفهوم التلقي ؟ وإذا كانت الإجابة بالإيجاب، فما هو دور المتلقي قديما وكيف أصبح دوره حديثا؟ إنّ طبيعة مقاربتنا للموضوع  "أفق التّلقي: بين الوصف البلاغي والوقع الجمالي –مقامات بديع الزمان أنموذجا-" أملت علينا دراسته وفق منهج وصفي تحليلي نقدي، حرصا من خلاله على الانطلاق من خطوة الوصف حيث تستجلي بفضلها بعض الأليات الفنية والّتي أفضت بدورها إلى الخطوة التّالية وهي خطوة التّحليل والنّقد من منظور آليات جمالية التلقي، إذ قمنا بامعان النظر في النّصوص والمعطيات المتوفرة ودراستها دراسة علمية ترمي لتحقق مبتغى هذا العمل. حدود الدّراسة: - التّلقي والقرآن الكريم/-التّلقي وعلم البلاغة في القرن 4 ه ـ-قراءة بلاغية لبعض مقامات الهمذاني- التّلقي ونظرية القراءة. قراءة موازية بين مقامة بديع الزّمان الهمذاني (357هـ-398هـ) في الشّرق ومقامة الشّيخ جمال الدّين الوهراني المتوفى سنة ت 575هـ في المغرب العربي.   وفي الأخير توصلت الدّراسة إلى النّتائج الآتية: إنّ حماسة النّقاد العرب اليوم لنّظرية التّلقي الغربية لا يجب أن يحجب عنا تلك الآراء النّقدية الرّائدة الّتي كانت لعلماء البلاغة قديما"، فالمتلقي لم يكن غائبا في وعي المبدع أو الناقد في التّراث البلاغي العربي بل كان له حضوره المتفاعل مع النّص، لقد تنبه البلاغيون منذ وقت مبكر إلى العلاقة الّتي تربط المتلقي بمؤلف النّص لكنها بقيت في حدود المفاهيم ولم ترقى إلى حدود المصطلحات القائمة في النّظريات النّقدية الحديثة الّتي احتفت بالمتلقي احتفاء كبيرا واعتبرته عنصرا فعالا وشريك للمبدع في العملية الابداعية. الكلمات المفتاحية:التّلقي، المتلقي،علم البلاغة ، جماليّة التّلقي، مقامات بديع الزّمان الهمذاني. Abstract :      The present study aims to identify the term "receive" in the process of the encounter that combines the reception in the Arabic dialect heritage, as a concept that shows the understanding of the quality of the relationship between the sender, the addressee, the message, the issue of influence and influence adopted by the Arab critics today, Among them is the conventional case of Western receiving theory (the German Constant School), a new model that began to impose itself on the field of aesthetic aesthetic studies through the Hermannotics of Receiving at Yaos and Finnomologia of Receiving at Aizer. This included the study study of the act of receiving as a human act In the light of the literary heritage, creativity is presented in the light of the establishment and the clarification of the interaction of certain concepts and terms of the phenomenon of reception , both ancient and modern.             The nature of our approach to the subject: "The horizon of reception: between the rhetorical description and the aesthetic impact - the buildings of Badi'zaman model - we hoped to study according to descriptive analytical method of cash, in order to get out of the step description, which is inspired by some technical mechanisms, which led us to the next step, Analysis and criticism from the perspective of aesthetic mechanisms of receipt, as we have carefully considered the texts and data available and studied a scientific study may achieve the purpose of this work.       The limits of the study: - Receive and the Holy Quran / - Receiving and science of rhetoric in the fourth century e - Reading the rhetoric of some of the sanctuaries of Hamdani - Receiving and reading theory. Reading parallel between the shrine of Badiezaman Hamzani (357 AH - 398H) in the east and the establishment of Sheikh Jamal Aldin Al-Wahrani, 575 e in the Arab Maghreb                                                                                                   Finally, the study reached the following results: The enthusiasm of Arab critics today for the theory of Western acceptance should not obscure from us the pioneering critical views that were the scholars of eloquence in ancient times. The recipient was not absent in the consciousness of the creative or critic of the Arabic rhetorical heritage, but rather had an interactive presence with the text. To the relationship between the recipient of the author of the text but remained within the limits of concepts did not live up to the limits of terminology existing in modern monetary theories that celebrated the recipient a great celebration and considered it an active element and partner of the creator in the creative process. Key words / Receive/ Receiver/ The art of eloquence/ Aesthetic of reception/ Maqamat of Badi 'al-Zaman al-Hamdhani.